The use of plant community attributes to detect habitat quality in coastal environments. (18th August 2015) - Del Vecchio, Silvia; Slaviero, Antonio; Fantinato, Edy; Buffa, Gabriella
Abstract : To detect changes in coastal ecosystems, we evaluated the variation over time in some vegetation features, such as species composition and structure (species richness, cover, growth forms). We found that ecological groups of species such as native focal species (species that provide essential ecological functions) and aliens (species that spread outside their natural distribution), and growth forms proved their efficacy in discriminating between habitat types and in describing their changes over time. The approach used in the current study may provide an instrument for the assessment of plant community quality that can be applied to other coastal ecosystems. Abstract: The monitoring of biodiversity has mainly focused on the species level. However, researchers and land managers are making increasing use of complementary assessment tools that address higher levels of biological organization, i.e. communities, habitats and ecosystems. Recently, a variety of frameworks have been proposed for assessing the conservation status of communities or ecosystems. Among the various criteria proposed, all the protocols suggest considering (i) spatial aspects (range and area), and (ii) qualitative aspects of specific structures and functions. However, changes to ecological function are difficult to quantify and many protocols end up by using qualitative criteria. The aim of this work was to test the efficacy of some plant community attributes for the detection of vegetation quality in sand dune plant communities. We chose plant community attributes that either help to distinguish a habitat from others (diagnostic components) or play a significant role in habitat function and persistence over time. We used a diachronic approach by contrasting up-to-date vegetation data with data from previous studies carried out within the same areas. Changes in species composition were detected through detrended correspondence analyses (detrended correspondence analyses), Multi-Response Permutation Procedures and Indicator Species Analysis, while structural changes were analyzed by comparing species richness, total species cover, ecological groups of species and growth forms through null models. Ecological groups such as native focal species and aliens, and growth forms proved their efficacy in discriminating between habitat types and in describing their changes over time. The approach used in this study may provide an instrument for the assessment of plant community quality that can be applied to other coastal ecosystems.